Improving patient safety by learning from near misses – insights from safety-critical industries - Woodier, Nicholas (2023)
Background Patients are at risk of being harmed by the very processes meant to help them. To improve patient safety, healthcare organisations attempt to identify the factors that contribute to incidents and take action to optimise conditions to minimise repeats. However, improvements in patient safety have not matched those observed in other safety-critical industries.